Functional divergence between morphs of a dwarf chameleon: differential locomotor kinematics in relation to habitat structure. (13th May 2015) - Higham, Timothy E.; Measey, G. John; Birn‐Jeffery, Aleksandra V.; Herrel, Anthony; Tolley, Krystal A.
<x xml:space="preserve">Abstract</x> Arboreal lizards are extremely effective at moving in structurally complex habitats, including surfaces of varying diameter and incline. Chameleons exemplify this by exhibiting a number of morphological specializations for moving in these habitats, including the use of prehensile feet and tail to grasp branches. Despite their unique morphology and behaviour, little is known about how locomotor movements vary between species. In addition, some species, such as the Cape Dwarf Chameleon, Bradypodion pumilum, consist of two morphs that differ in ecology, morphology, and behaviour. The two morphs can be found in either closed canopy woodland habitat or relatively open fynbos habitat. The morph that occupies the woodland habitat tends to be larger and utilizes larger diameter perches. Although their ecological and morphological divergence is established, whether this translates into differences in three‐dimensional kinematics of locomotion is not known. Given the potentially strong selective pressures from structurally different habitats, kinematic differences might reveal the functional basis of incipient speciation. We determined that the two morphs diverge significantly in multidimensional kinematic space, and that this occurs for the forelimb and hindlimb independently. These differences outweigh the effects of substrate within each morph, although the differences between morphs were more pronounced on the vertical treatments.